1978
DOI: 10.1113/jphysiol.1978.sp012273
|View full text |Cite
|
Sign up to set email alerts
|

Calcium transients in isolated amphibian skeletal muscle fibres: detection with aequorin.

Abstract: SUMMARY1. Single twitch muscle fibres isolated from frogs and toads were microinjected with the Ca2+-sensitive bioluminescent protein aequorin. The fibres contracted normally and emitted flashes of light (aequorin responses) in response to stimulation for many hours thereafter.2. No luminescence was detected from healthy fibres at rest. 3. The aequorin diffused from the site of injection at a rate consistent with a diffusion coefficient of 5 x 10-8 cm2/sec.4. During trains of isometric contractions there was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
270
3
2

Year Published

1980
1980
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 462 publications
(311 citation statements)
references
References 42 publications
35
270
3
2
Order By: Relevance
“…The calcium transients during repetitive stimulation and tetanus were also investigated by MILEDI et al (1982) in frog's twitch muscle by using arsenzao III. In agreement with BLINKS et al (1978) they observed a negative staircase of the amplitude of light response together with slowing of its decay (summation). In this respect, the recent observation by HOMSHER and KEAN (1977) that the activation heat per stimulus declined with decrease in the stimulus interval would be interesting.…”
Section: Effects Of Twitch On Tetanus 445supporting
confidence: 70%
See 1 more Smart Citation
“…The calcium transients during repetitive stimulation and tetanus were also investigated by MILEDI et al (1982) in frog's twitch muscle by using arsenzao III. In agreement with BLINKS et al (1978) they observed a negative staircase of the amplitude of light response together with slowing of its decay (summation). In this respect, the recent observation by HOMSHER and KEAN (1977) that the activation heat per stimulus declined with decrease in the stimulus interval would be interesting.…”
Section: Effects Of Twitch On Tetanus 445supporting
confidence: 70%
“…The effect may not interfere with the progressing positive staircase per se, within a certain limit of number of stimuli, but could well influence the following tetani by decreasing the supply of activator calcium to the releasing sites. Applying calcium-sensitive bioluminescent aequorin, BLINKS et al (1978) measured the calcium transients in the single twitch muscle fiber of frog and observed a descending staircase of the peak-light intensity when repetitive stimulation was applied. This was interpreted as reflecting a gradual decline of sequestration of calcium by the sarcoplasmic reticulum.…”
Section: Effects Of Twitch On Tetanus 445mentioning
confidence: 99%
“…In addition the relation between the fall of free Ca 2+ and rate of relaxation has been studied in intact muscle fibres [13,[16][17][18] but these studies on relaxation are limited by the rate at which free calcium can be removed from the sarcoplasm, presumably mainly by the activity of the sarcoplasmic reticulum calcium pump (14 s -1 at 10°C [14] or 25 s -1 following a single twitch decreasing to 10 s -1 after a tetanus of at least 2 s duration [13]). There is also an elevation or 'tail' to the free calcium fall which extends over 5 s in frog at 10°C [13] or 1-2 s in arthropod fibres at 20°C [18].…”
Section: Discussionmentioning
confidence: 99%
“…The micropipette (arrow) and the tail of the cell are shown by raising the background illumination (A) . The damage response involves an intensive but localized rise in the free calcium ion concentration (8), which causes cortical contraction. Recorded in 1/60 s. luminescence in the tail (I-5-s duration) (Fig.…”
Section: Stimulated Pulses Of Luminescencementioning
confidence: 99%
“…The high signal to noise ratio, relative specificity for Ca", lack of toxicity, and ease of signal detection have made this technique attractive for the study of cells containing low free calcium ion concentrations . Aequorin luminescence has already been applied successfully to other motile processes, including the contraction of muscle (3,4,8,23), shuttle streaming in Physarum polycephalum (58), fertilization of Medaka eggs (59), and the contraction of Spirostomum (26) .…”
mentioning
confidence: 99%